Evaluation of Online Learning Processes in FKIP Universitas Lampung During Covid-19 Pandemic - Riyanda, Afif Rahman; Ambiyar, Ambiyar; Syahril, Syahril; Fadhilah, Fadhilah; Samala, Agariadne Dwinggo; Adi, Novi Hendri; Aminuddin, Fattachul Huda (Jurnal Pendidikan MIPA, 2021)
This article aims to explain the evaluation of the online learning process during the COVID-19 pandemic at the teaching and education faculty of the University of Lampung using the CIPP model. From this study, it can be concluded that the level of achievement of the implementation of the online learning process on the context component obtained an average score of 4.17 (83.59%) with a good category; the input component obtained an average score of 3.973 (80.04%) with good category; the process component obtained an average score of 3,798 (76.88%) with sufficient category. This means that the implementation of online learning is still not able to overcome obstacles such as the uneven distribution of internet services that can be accessed by students in the application of online learning. as well as the speed of internet network access which is still slow and product components that get an average score of 4,107 (82.13%) in the good category. From the results of the study, it can be concluded that the implementation of online learning during the COVID-19 pandemic is quite good.Keywords: online learning, Covid-19 pandemic, CIPP Model. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp179-187